2020
DOI: 10.3390/plants9020188
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Cadmium Tolerance in Rice: Insight into Vanillic Acid-Induced Upregulation of Antioxidant Defense and Glyoxalase Systems

Abstract: Cadmium (Cd) is a toxic heavy metal that enters the human food chain from the soil via plants. Increased Cd uptake and translocation in plants alters metabolism andreduces crop production. Maintaining crop yield therefore requires both soil remediation andenhanced plant tolerance to Cd. In this study, we investigated the effects of vanillic acid (VA) on Cd accumulation and Cd stress tolerance in rice (Oryza sativa L. cv. BRRI dhan54). Thirteen-day-old rice seedlings treated with CdCl2 (1.0 and 2.0 mM) for 72 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 66 publications
4
15
0
Order By: Relevance
“…The COU pre‐treatment not only reduced the ROS level (indicated by biochemical and histochemical detection of H 2 O 2 ) and lipid peroxidation but also enhanced membrane stability. Similarly, alleviation of oxidative stress in plants through exogenous phenolic compounds has been reported previously (Li et al 2013; El‐Soud et al 2013; Ozfidan‐Konakci et al 2019; Parvin et al 2019a; Bhuyan et al 2020).…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…The COU pre‐treatment not only reduced the ROS level (indicated by biochemical and histochemical detection of H 2 O 2 ) and lipid peroxidation but also enhanced membrane stability. Similarly, alleviation of oxidative stress in plants through exogenous phenolic compounds has been reported previously (Li et al 2013; El‐Soud et al 2013; Ozfidan‐Konakci et al 2019; Parvin et al 2019a; Bhuyan et al 2020).…”
Section: Discussionsupporting
confidence: 65%
“…However, higher GST activity induced by salt increased with COU pre-treatment, while GST also performs a detoxification function through increasing plant stress tolerance. Similar to COU, both VA and Qu also gave similar results in stress-affected plants (Parvin et al 2019a(Parvin et al , 2020Bhuyan et al 2020).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…It has been reported that metals such as cadmium and arsenate can cause an increase in GPX activity while reducing GST activity indicating that there was no detoxification of lipid peroxidation in exposed rice ( Oryza sativa L. cv. BRRI dhan54) plants [ 78 ].…”
Section: The Influence Of Salicylic Acid On Abiotic Stress Tolerance In Ricementioning
confidence: 99%
“…Moreover, mitigating effects of NaHS have been further up-scaled by antioxidant activity and osmotic adjustment to minimize membrane oxidative damage. Methylglyoxal (MG), a cytotoxic metabolic by-product of glycolytic pathways, usually interacts with macromolecules to trigger protein inactivation and induces oxidative damages to plant under abiotic stress, such as heavy metals ( Hoque et al, 2016 ; Bhuyan et al, 2020 ). In maize, Cr tolerance of young seedlings was linked to the suppression of NADPH oxidase activity, resulting in restricted ROS accumulation following exogenous application of NaHS ( Kharbech et al, 2020 ).…”
Section: Exogenous H 2 S Application: a Precursor mentioning
confidence: 99%